Special aspects for organization of correctional work with the children, that a have deviations of intellectual development in the conditions of general educational institution (Actual Problems of Psychology in Educational Institutions, 2020)
Abstract. The article considers critical moments of integration the childrenwith intellectual deviations into the environment of comprehensive schoolwith implementation of inclusive education. The ideas of equality to allthe members of society regardless their nationality, gender, race, culture,social position, religion and the individual abilities & capabilities are putin the basis of inclusive education. It is emphasized in the article on thepeculiarities of organization of the correction works for the children withintellectual deviations and also there are described the ways of realizationthe correctional clause in the conditions of general education institution.According to results of the theoretical-methodological analysis that wasperformed by the authors, it is provided the opinion of the resource teachersabout the features of the process of correctional studies & the child guidancefor the kids with intellectual deviations. The major point to proceed witheffective inclusive education for the children with the intellectual deviationsis the development of methods, methodologies actions and principles ofspecial didactics in the educational-integration process. The correction —developing studies foresees the intensified works for the corrections ofpsychological functions, educational activities, the communicative skills,and the developing of skills, abilities & capabilities for children in theprocess of manual training
Keywords: children with special educational requirements; children with intellectual deviations; inclusion; inclusive education; correction-developing work; multidiscipline team; supervision